Elucidating the pharmacodynamic mechanisms of Yuquan pill in T2DM rats through comprehensive multi-omics analyses - Lei, Yan; Huang, Jianmei; Xie, Zhongshui; Wang, Can; Li, Yihong; Hua, Yutong; Liu, Chuanxin; Yuan, Ruijuan (Frontiers in Pharmacology, 2023)
Background: Yuquan Pill (YQW) is a modern concentrated pill preparation of six herbs, namely, Ge Gen (Pueraria lobata Ohwi), Di huang (Rehmannia glutinosa Libosch.), Tian Huafen (Trichosanthes kirilowii Maxim.), Mai Dong (Ophiopogon japonicus (L. f.) Ker Gawl.), Wu Weizi (Schisandra chinensis (Turcz.) Baill.) and Gan Cao (Glycyrrhiza uralensis Fisch.). It is extensively used to treat type 2 diabetes-related glucose and lipid metabolism disorders. But what’s the pharmacodynamic substance and how it works in the treatment of Type 2 diabetes mellitus (T2DM) are still unclear. Purpose: The purpose of this study is to determine the likely pharmacological components and molecular mechanism of YQW’s intervention on T2DM by combining serum pharmacochemistry, network analysis and transcriptomics. Methods: The efficacy and prototypical components of blood entry were determined after oral administration of YQW aqueous solution to T2DM rats induced by high-fat feed and low-dose streptozotocin (STZ), and the key targets and pathways for these compounds to intervene in T2DM rats were predicted and integrated using network analysis and transcriptomics techniques. Results: In diabetic rats, YQW can lower TG, CHO, NO, and MDA levels (p < 0.05) while increasing HDL-C levels (p < 0.01), and protecting the liver and kidney. 22 prototype components (including puerarin, daidzein, 3′-methoxypuerarin, and liquiritigenin, among others) were found in the serum of rats after oral administration of YQW for 90 min, which might be used as a possible important ingredient for YQW to intervene in T2DM rats. 538 YQW pharmacodynamic components-related targets and 1,667 disease-related targets were projected through the PharmMapper database, with 217 common targets between the two, all of which were engaged in regulating PI3K-Akt, MAPK, Ras and FoxO signal pathway. Finally, the mRNA expression profiles of liver tissues from rats in the control, model, and YQW groups were investigated using high-throughput mRNA sequencing technology. YQW can regulate the abnormal expression of 89 differential genes in a disease state, including 28 genes with abnormally high expression and 61 genes with abnormally low expression. Five common genes (Kit, Ppard, Ppara, Fabp4, and Tymp) and two extensively used regulatory pathways (PI3K-Akt and MAPK signaling pathways) were revealed by the integrated transcriptomics and network analysis study. Conclusion: The mechanism of YQW’s intervention in T2DM rats could be linked to 22 important components like puerarin, daidzein, and glycyrrhetinic acid further activating PI3K-Akt and MAPK signaling pathways by regulating key targets Kit, Ppard, Ppara, Fabp4, and Tymp, and thus improving lipid metabolism disorder, oxidative stress, and inflammation levels in T2DM rats. On the topic, more research into the pharmacological ingredient foundation and mechanism of YQW intervention in T2DM rats can be done.